From Environmental Loss to Resistance : Infrastructure and the Struggle for Justice in North America - Rekow, Lea; Loadenthal, Michael (Book collections on Project MUSE., 2020)
"North Americans have reached a socioenvironmental tipping point and stand at a critical juncture where social transformation has become necessary to secure a stable and desirable future. As hurricanes destroy coastal areas that once hosted schools and homes, petroleum refineries choke nearby communities and their parks, and pipeline construction threatens water rights for indigenous peoples, communities are left to determine how to best manage and mitigate environmental loss. In this new collection, a range of contributors-among them researchers, practitioners, organizers, and activists-explore the ways in which people counter or cope with feelings of despair, leverage action for positive change, and formulate pathways to achieve environmental justice goals. These essays pay particular attention to issues of race, class, economic liberalization, and geography; place contemporary environmental struggles in a critical context that emphasizes justice, connection, and reconciliation; and raise important questions about the challenges and responses that concern those pursuing environmental justice. Contributors include the volume editors, Carol J. Adams, Randall Amster, Jan Inglis, Eileen Delehanty Pearkes, Zoë Roller, and Michael Truscello"--